A contribuição de ferramentas e práticas de gestão da qualidade, tecnologia e conhecimento para a evolução do nível de maturidade do processo de distribuição de energia elétrica no Brasil: a percepção do cliente e do gestor do processo - Gueiber, Daniel (2009)
The current world scenario determines that the procedures carried out by undertakings occur at levels of excellence and with the permanent search for continuous improvement. In this situation it is crucial that is verified using tools and quality management practices, knowledge and technology in development. With the purpose to verify the effective application of these tools, this work were confronted the customer perceptions, who receiving the products and services, as the managers who make the management of processes. Search for the development of a specific procedure was used, the distribution of electrical energy, which is based on a model international adapted for Brazilian reality, with competitive referential held by ANEEL - National Electrical Energy Agency. So two searches: the IASC - Index ANEEL of Customer Satisfaction Customers, and another held with managers, which was used instrument based on criteria of PNQ - National Quality Award. The first survey assessed the customer perception, covering the search results in Brazilian territory. The second survey assessed the potential of tools, using a population of managers and specialists, a distributor of Centre South Brazil, enterprise search and winning participant in three editions of the IASC Prize. The model used for application assessment tools and practices was prepared on the basis of criteria of PNQ and verified on each of the steps the care requirements of ISO9001: 2000 and CMMI - Capability Maturity Model Integration, seeking to verify process maturity. This instrument has enabled the viewing of gaps, both in customer perception and manager perception. The tools and practices to fill these gaps were obtained through the instrument built in requirements of ISO9001 and CMMI and indicated for each stage of the process. This confrontation has strong correlation between perceived gaps and potential for improvement made, given both the purpose of verifying the application of tools, as well as indicate those able to contribute to the improvement of the process.